Institutional and behaviour-change interventions to support COVID-19 public health measures: a review by the Lancet Commission Task Force on public health measures to suppress the pandemic. Issue 5 (11th May 2021) - Lee, Jong-Koo; Bullen, Chris; Ben Amor, Yanis; Bush, Simon R; Colombo, Francesca; Gaviria, Alejandro; Karim, Salim S Abdool; Kim, Booyuel; Lavis, John N; Lazarus, Jeffrey V; Lo, Yi-Chun; Michie, Susan F; et al.
Abstract: The Lancet COVID-19 Commission Task Force for Public Health Measures to Suppress the Pandemic was launched to identify critical points for consideration by governments on public health interventions to control coronavirus disease 2019 (COVID-19). Drawing on our review of published studies of data analytics and modelling, evidence synthesis and contextualisation, and behavioural science evidence and theory on public health interventions from a range of sources, we outline evidence for a range of institutional measures and behaviour-change measures. We cite examples of measures adopted by a range of countries, but especially jurisdictions that have, thus far, achieved low numbers of COVID-19 deaths and limited community transmission of severe acute respiratory syndrome coronavirus 2. Finally, we highlight gaps in knowledge where research should be undertaken. As countries consider long-term measures, there is an opportunity to learn, improve the response and prepare for future pandemics.